A mixture of mischief - Meriano, Anna (Meriano, Anna. Love sugar magic, 2020)
"It's spring break in Rose Hill, Texas, but Leo Logroño has a lot of work to do if she's going to become a full-fledged bruja like the rest of her family. She still hasn't discovered the true nature of her magical abilities, and that isn't the only bit of trouble in her life: Her family's baking heirlooms have begun to go missing, and a new bakery called Honeybees has opened across town, threatening to run Amor y Azúcar right out of business. What's more, everyone around her seems to have secrets, and none of them want to tell Leo what's going on. But the biggest secret of all comes when Leo is paid a very surprising visit--by her long-lost Abuelo Logroño. Abuelo promises answers to her most pressing questions and tells Leo he can teach her about her power, about what it takes to survive in a world where threats lurk in the shadows. But can she trust him?" --